Proceedings of the 10th International Conference on Human Computer Interaction With Mobile Devices and Services 2008
DOI: 10.1145/1409240.1409249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile map orientation and tactile feedback on navigation speed and situation awareness

Abstract: Mobile information systems aid first responders in their tasks. Support is often based on mobile maps. People have different preferences for map orientations (heading-up or north-up), but map orientations also have different advantages and disadvantages. In general north-up maps are good for building up situation awareness and heading-up maps are better for navigational tasks. Because of heavily loaded visual modalities, we expect that tactile waypoint information can enhance navigation speed and situation awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Since way finding based on survey knowledge (e.g., the paper map) relies on being spatially oriented [12] the in average shorter routes indicate that the participants had a better spatial orientation when provided with the tactile cue. This also supports the findings by Smets et al [16] where participants in a virtual world navigated more effectively with a vibrotactile directional cue of the destination. Nevertheless, the walking speed decreased significantly while the completion time was not significantly different with the tactile belt.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Since way finding based on survey knowledge (e.g., the paper map) relies on being spatially oriented [12] the in average shorter routes indicate that the participants had a better spatial orientation when provided with the tactile cue. This also supports the findings by Smets et al [16] where participants in a virtual world navigated more effectively with a vibrotactile directional cue of the destination. Nevertheless, the walking speed decreased significantly while the completion time was not significantly different with the tactile belt.…”
Section: Discussionsupporting
confidence: 90%
“…Tactile displays that convey spatial information for improving the sense of orientation [21,10,23] or the situation awareness [8,16] have been investigated for quite a while. Tactile belts, such as the ActiveBelt by Tsukada and Yasumura [18], consist of a number of tactors (e.g.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This kind of information presentation technique has successfully been used to "drag" people towards waypoints [28] while reducing the distraction at the same time [3,14]. With respect to map-based navigation it has been shown that cueing the general direction of the destination can improve the navigation performance and reduce the distraction [15,22]. Supporting map-based navigation is desirable, since turn-by-turn instructions may disengage users from the environment [9], lead to a worse understanding of the environments spatial layout [1], and are not necessarily more effective than maps [7].…”
Section: Figmentioning
confidence: 99%